Th1/17-Biased Inflammatory Environment Associated with COPD Alters the Response of Airway Epithelial Cells to Viral and Bacterial Stimuli - Yifan Chen; Rakesh K. Kumar; Paul S. Thomas; Cristan Herbert (Mediators of Inflammation)
Chronic obstructive pulmonary disease (COPD) is characterized by airway inflammation associated with a Th1/17-biased cytokine environment. Acute exacerbations of COPD (AECOPD) are most often triggered by respiratory infections, which elicit an exaggerated inflammatory response in these patients, via poorly defined mechanisms. We investigated the responses of airway epithelial cells (AECs) to infective stimuli in COPD and the effects of the Th1/17-biased environment on these responses. Cytokine expression was assessed following exposure to virus-like stimuli (poly I:C or imiquimod) or bacterial LPS. The effects of pretreatment with Th1/17 cytokines were evaluated in both primary AECs and the Calu-3 AEC cell line. We found that poly I:C induced increased expression of the proinflammatory cytokines IL1β, IL6, CXCL8, and TNF and IFN-β1 in AECs from both control subjects and COPD patients. Expression of IL1β in response to all 3 stimuli was significantly enhanced in COPD AECs. Primary AECs pretreated with Th1/17 cytokines exhibited enhanced expression of mRNA for proinflammatory cytokines in response to poly I:C. Similarly, Calu-3 cells responded to virus-like/bacterial stimuli with increased expression of proinflammatory cytokines, and a Th1/17 environment significantly enhanced their expression. Furthermore, increased expression of pattern recognition receptors for viruses (TLR3, TLR7, IFIH1, and DDX58) was induced by Th1/17 cytokines, in both primary AECs and Calu-3 cells. These findings suggest that the Th1/17-biased environment associated with COPD may enhance the proinflammatory cytokine response of AECs to viral and bacterial infections and that increased signaling via upregulated receptors may contribute to exaggerated inflammation in virus-induced AECOPD.